2020
DOI: 10.3390/ijerph17197235
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Function and Its Association with the Severity of Menopause-Related Symptoms

Abstract: The aim of this study was to examine female sexual functioning and its association with the impact of the symptoms of menopause among Spanish postmenopausal women. A total of 182 postmenopausal women (65.59 ± 7.93 years) participated in this cross-sectional study. The female sexual function index (FSFI) and the menopause rating scale (MRS) were used to analyze sexual function and severity of menopausal symptoms, respectively. Age, education, area of residence, occupation, and depression (Hospital Anxiety and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
4
13
0
Order By: Relevance
“…The results of the present study showed that there is a significant negative correlation between the age of the spouse and the sexual function of postmenopausal women. This result is consistent with some other studies [ 12 , 41 , 43 , 46 ]. This association may be due to hormonal changes due to aging and its consequences on sexual partner sexual function [ 12 ], which in turn may affect female sexual function.…”
Section: Discussionsupporting
confidence: 94%
“…The results of the present study showed that there is a significant negative correlation between the age of the spouse and the sexual function of postmenopausal women. This result is consistent with some other studies [ 12 , 41 , 43 , 46 ]. This association may be due to hormonal changes due to aging and its consequences on sexual partner sexual function [ 12 ], which in turn may affect female sexual function.…”
Section: Discussionsupporting
confidence: 94%
“…Zeleke et al reported low sexual desire in 88.0% of older women [40]. Decreased sexual function in postmenopausal women was also confirmed in a recent study by Pérez-Herrezuelo et al [41]. Overall, from the literature, it is clear that an association exits between older age and lowered sexual desire.…”
Section: Discussionmentioning
confidence: 71%
“…Increasing age had been a concern among Turkish women where 46–55 years age group presented the highest prevalence rate of FSD, 67.9% [ 33 ]. Postmenopausal women residing in a rural area were linked to having better sexual function from a study in Granada, Spain [ 34 ]. Apart from that, multiparity is a significant risk factor for FSD.…”
Section: Discussionmentioning
confidence: 99%